Assessment of Security Design Strategies in Resorts Design in Osun State, Nigeria - Abdullahi, Aisha P.; Abiodun, Timothy O.; Morakinyo, Kolawole O.; Adedayo, Olatunde F.; Akande, Nneka O. (ARCHIHUMANUM, 2024)
Security has become an issue that has been reoccurring especially in the current state of the country which raises concern for the design of resorts within the nation and the challenges should be considered and gotten a solution for as soon as possible. The aim of this study is to assess security strategy design in resort design. The research method used in this study is the qualitative method and the use of observation check list has been adopted in obtaining information. The observation schedule was used as an instrument to collect data and the data were used as sampling method. These data were analyzed with content analysis and the findings showed that security measures have not been properly adopted in the resort design and most resorts do not take into consideration the necessary design strategies which has automatically open them to external threats. The research recommends that the need to design with consideration of security should be of uttermost importance in designing resort based on the number of people going and the function of the building and to urge other designers to consider the requirements while designing.